1989
DOI: 10.1099/00221287-135-11-2899
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Root Tips as a Vector for Passive Vertical Transfer of Azospirillum brasilense Cd

Abstract: The ability of wheat root tips to serve as efficient vertical vectors for passive transfer of Azospirillum brasilense Cd was evaluated in sterilized growth chambers containing agar, sand or soil. Most root tips, whether from main or lateral roots, were colonized by A . brasilense Cd and were capable of transferring this bacterium to a depth of 290 mm from the inoculation site. The location of A. brasilense Cd was directly dependent on root tip location; whenever root tips passed through a bacterial layer, rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Nevertheless, Pseudomonas strains r2r, erl2r and esNr were numerous in the distal third but not in the middle third of one of the replicate plants. This pattern of colonization is consistent with the view that bacteria are transported with the growing root tip, as observed by Elad and Chet (1987) and Bashan and Levanony (1989). However, such transport occurs infrequently and perhaps only with certain bacteria.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, Pseudomonas strains r2r, erl2r and esNr were numerous in the distal third but not in the middle third of one of the replicate plants. This pattern of colonization is consistent with the view that bacteria are transported with the growing root tip, as observed by Elad and Chet (1987) and Bashan and Levanony (1989). However, such transport occurs infrequently and perhaps only with certain bacteria.…”
Section: Discussionsupporting
confidence: 76%
“…The bacteria inoculated on seeds in this study remained primarily in the upper region of the rhizosphere. Similar results have been reported by Chao et al (1986) and Bahme and Schroth (1987), but seed-inoculated bacteria sometimes develop throughout the rhizosphere (Bashan and Levanony, 1989;Kloepper et al, 1980). To determine whether a factor other than movement from the seed limited colonization of distal sections of the rhizosphere, bacteria were inoculated throughout the soil, and their subsequent location in the rhizosphere was determined.…”
Section: Discussionmentioning
confidence: 53%
“…The bacterial density per gram of plant tissue was *100 times higher for bacteria isolated from inner tissues of roots than those present in the first stolon; and the fact that we could not isolate Azospirillum from the third stolon in the cultivar Camarosa, may be due to the ratio of stolons growth rate versus velocity of bacterial translocation through inner tissues. In this context, we should assume that the stolon growth rate is higher than the bacterial translocation rate, although some earlier information about transportation of Azospirillum in growing roots (not stolons) showed that Azospirillum translocates faster than wheat growing roots, irrespective of the root growth rate (Bashan and Levanony 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the results indicates that all of our test bacteria were able to colonize and grow throughout a developing wheat rhizosphere, but to di¡erent extents. Di¡erences in colonization probably resulted from di¡erences in bacterial species ability to adhere to the root tip, utilize plant exudates and/or a lack of motility [41,42]. However, addition of live nematodes to our system substantially increased the degree of colonization for all test bacteria.…”
Section: Discussionmentioning
confidence: 99%